Colon Capsule Endoscopy for Inflammatory Bowel Disease - Naoki Hosoe; Yukie Hayashi; Haruhiko Ogata (Clinical Endoscopy, 2020)
Colon capsule endoscopy was initially introduced in 2006. Since the results of a prospective study to evaluate first-generation colon capsule endoscopy efficacy for the detection of colonic neoplasia were unsatisfactory, second-generation colon capsule endoscopy was developed and reported in 2009. In this review article, we provide an overview of the current state of colon capsule endoscopy for evaluation of inflammatory bowel disease in a clinical setting and describe our clinical experience with this technology and its application. Among the various types of inflammatory bowel diseases, ulcerative colitis is the primary target for application of colon capsule endoscopy. Nevertheless, the initial results of studies using first-generation colon capsule endoscopy to evaluate inflammation were unclear. More recently, second-generation colon capsule endoscopy has provided higher accuracy for assessment of inflammation in patients with ulcerative colitis. Colon capsule endoscopy enables noninvasive observation (with reduced volume preparation) of mucosal inflammation severity in patients with ulcerative colitis.